Chapter After Picasso: Reinterpretations and recreations of Les Demoiselles D'Avignon in Contemporary Art - Méndez Baiges, Maite (Studi e saggi, 2022)
Another way of showing interpretations of Picasso's Demoiselles is to heed the replicas, copies, pictorial or artistic versions made by contemporary artists. This chapter presents the artistic versions of the work done by artists at the end of the 20th and start of the 21st century. It begins the pop replicas by Caulfield or Equipo Crónico and the appropriationists like Richard Prince or Mark Bidlo. And continuing with those done by feminist or Afroamerican artists like Faith Ringgold or the queer versions of Rafael Agredano. Finally it deals with the geographical and culturally situated critical proposals of Francis Alÿs or Rogelio López Cuenca/Elo Vega.